Lacked of Breast Cancer Awareness of Indonesian Rural Women: A Descriptive Study to Adult Women in District Pangandaran, Indonesia - Alfarafisa, Nayla M.; Bashari, Muhammad H.; Usman, Hermin A.; Nurcahyani, Arima KSD; Pramesti, Defi A.; Azizah, Dika WN.; Yuliani, Lala; Rakhman, Putri HA.; Huda, Fathul (Universitas Padjadjaran, Indonesia, 2023)
Breast cancer remains a significant global health challenge, particularly in low and middle-income countries like Indonesia. Patients with advanced metastatic breast cancer have a dismal prognosis. A cancer promotion program’s failure can be attributed to low awareness of breast cancer. This descriptive study aimed to evaluate breast cancer awareness among adult women in District Pangandaran, Indonesia. Data was gathered in July 2018 from 189 individuals using a verified Breast Cancer Awareness Measure instrument developed by Cancer Research UK. Results revealed a concerning lack of awareness among participants regarding various breast cancer risk factors, symptoms, and screening practices. Additionally, reluctance to seek medical help due to fear of diagnosis was observed, particularly among housewives without health insurance. These findings highlight the urgent need for comprehensive health programs to enhance breast cancer awareness and promote early detection strategies tailored to the Indonesian population, especially in rural areas. Healthcare providers and public health workers play a vital role in this effort, along with implementing innovative health promotion policies by the government to improve cancer prevention programs.